Development of ionic liquid crystals based on pyridinium and picolinium cations - Santos, Andreia F. M. (2023)
This work was financially supported by the Associate Laboratory for Green project number [PTDC/EAM-AMB/2023/2021] financed by National Funds through FCT-MCTES and POR Lisboa 2020. Firstly, I would like to express my gratitude to my PhD supervisors (Prof. Luis C. Branco, Prof. Madalena Dionísio and Prof. Maria H. Godinho) for their guidance, inspiration and support throughout my doctoral project. I am also grateful for the fruitful discussions and help provided by Prof. João L. Figueirinhas and Prof. C. J. Dias. Publisher Copyright: © 2023 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.